Biological targets and mechanisms of action of natural products from marine cyanobacteria. Issue 3 (26th March 2015) - Salvador-Reyes, Lilibeth A.; Luesch, Hendrik
<x xml:space="preserve">Abstract</x> Diversification of the screening platform coupled with innovative adaptation to natural products derived from marine cyanobacteria led to the characterization of intriguing mechanisms of action and a powerful display of potent bioactivities.